SYNTHESIS OF OXIDE MATERIAL SR2SNO4:TI4+ BY SONOCHEMISTRY METHOD: EFFECT OF BASE AND SOLUTION CONCENTRATION VARIATION - SEPTIANY (NIM : 10508085); Pembimbing : Dr. Bambang Prijamboedi, LIANY
Luminescent materials or called as phosphors materials have been used on various display devices and luminescent application such as Plasma Display Panels (PDP). One of the candidate as phosphors materials is metals oxide strontium stannate (Sr2SnO4) which has semiconductor properties and wide band gap of ~4.5 eV. Impurities such as transition metal ion and rare earth ion can be used as luminescence activator. In this research, Sr2Sn1-xTixO4 (x = 0.05) synthesized by sonochemistry method with variations of base (NaOH/NH4OH), concentration of Sn4+ on the solution (M = 0.4, 0.5, 0.66 mol/L) and sintering temperature (T = 600, 800, 1000, 1400 oC). Difractogram obtained showed that NH4OH gives SrSnO3 as dominant phase, whereas NaOH gives Sr2SnO4 as dominant phase. Difractogram also showed sample with low intensity of impurities is given by sample variation 2 NaOH. Difractogram sample from various sintering temperature show that temperature when Sr2SnO4 become dominant phase is at 1000 oC. Photoluminescence properties also determined with radiation of UV light with range of λexcitation = 200Ã‚Â–400 nm. All samples show high emission intensity at λemission = 500Ã‚Â–510 nm which is in cyan colour region. Then, intensity of all samples compared on λexcitation = 295nm and sample that showed the highest intensity is given by sample variation 3 NaOH. From excitation spectrum of all samples showed two peaks with high intensity at 4.2 eV and 5 eV. Fitting results show two peaks with high intensity at 2.3eV and 2.45eV which indicated that there is 2 emission peaks in this oxide.